2021
DOI: 10.29244/avi...137-141
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and The Habitat Characteristics of Anopheles vagus (Diptera: Culicidae) Larvae at Paddy Fields in The Vicinity of Dramaga IPB University Campus Dramaga Bogor West Java

Abstract: Dramaga sub-district is an area that has rice fields close to buffalo stalls and a population of wild Macaca fascicularis as natural hosts for several species of Plasmodium. This causes the Dramaga sub-district to become a potential vector habitat for malaria, including Anopheles vagus. This study aims to analyze distribution of An. vagus larval stage in 4 villages (Cikarawang, Babakan, Margajaya, and Ciherang) in Dramaga subdistrict which have paddy field areas. Larvae were collected using a dipper, and each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This report is consistent with the finding of the study conducted in Seram, Maluku (19). Several habitats such as rice fields (20), ponds (21), puddles of flooded soil, grassy fields with shrubs and shade plants that hold water, and even dug wells are breeding places for A. vagus (22). The ditch around the settlement ( 21) collects rainwater and household waste overgrown with tall grass is also favored by this species (23), especially those with a mud bottom (24) (25).…”
Section: Discussionsupporting
confidence: 89%
“…This report is consistent with the finding of the study conducted in Seram, Maluku (19). Several habitats such as rice fields (20), ponds (21), puddles of flooded soil, grassy fields with shrubs and shade plants that hold water, and even dug wells are breeding places for A. vagus (22). The ditch around the settlement ( 21) collects rainwater and household waste overgrown with tall grass is also favored by this species (23), especially those with a mud bottom (24) (25).…”
Section: Discussionsupporting
confidence: 89%
“…The phylogenetic tree reconstruction of all isolates compared with that of other simian and human Plasmodium isolates in GenBank showed that all isolates clustered as P. inui ( Figure-4 ). The isolates had the closest relationship with the P. inui isolate from South China isolated from Macaca fascicularis in South China in 2011 (HM032051) [ 10 ] and grouped with other P. inui such as P. inui isolated from wild M. fascicularis from Thailand (EU400387), Macaca cyclopis (AB287276), and Macaca mulatta (U72541).…”
Section: Resultsmentioning
confidence: 99%
“…P. inui is the most widely distributed malaria parasite in Old World monkeys and is naturally found in M. fascicularis , Macaca nemestrina , Macaca mulatta , Macaca radiata , M. cyclopis , Cynopithecus niger , Presbytis obscurus , and Pavo cristatus [ 15 ]. Regarding the potential zoonosis of P. inui for human health, whether this simian parasite poses a danger of cross-contamination to humans is unknown and requires further investigation in more monkey populations, human populations, and malaria vectors [ 10 ]. Although P. inui is experimentally transmissible to humans, natural human infections have not yet been reported or documented in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation